Driving factors of direct greenhouse gas emissions from China's pig industry from 1976 to 2016 - Xiao-wen Dai; Zhanli Sun; Daniel Müller (Journal of Integrative Agriculture, 2021)
Livestock cultivation is a significant source of greenhouse gas (GHG) emissions, accounting for 14.5% of the total anthropogenic emissions. China is responsible for a considerable share of the global livestock emissions, particularly caused by pork production. We used the Kaya identity and the logarithmic mean Divisia index (LMDI) to decompose the national annual GHG emissions from enteric fermentation and manure management in pig farming in China from 1976 to 2016. We decomposed the sources of the emissions into five driving factors: (1) technological progress (e.g., feed improvement); (2) structural adjustment in the livestock sector; (3) structural adjustment in agriculture; (4) affluence; and (5) population growth. The results showed that the net GHG emissions from the pig sector in China increased 16 million tons (Mt) of carbon dioxide equivalents (CO2eq) during the study period. The decomposition analysis revealed that structural adjustment in agriculture, growing affluence, and population growth contributed to an increase of the GHG emissions of pork production by 23, 41, and 13 Mt CO2eq, respectively. The technological progress and structural changes in animal husbandry mitigated emissions by –51 and –11 Mt CO2eq, respectively. Further technological progress in pig production and optimizing the economic structures are critical for further reducing GHG emissions in China's pig industry. Our results highlight the dominant role of technological changes for emission reductions in the pig farming.
Keywords: 630; livestock production; carbon emissions; manure management; pig farming; LMDI decomposition